Christianised rationalism a reply to Professor Harnack's "What is Christianity?" - Anderson, Robert, 1841-1918 (London, UK John F. Shaw, 1903)
Includes biliographical references.
Brethren writer.
Keywords: Harnack, Adolf, -- 1851-1930; Christianity -- interpretation, criticism, etc